Inter-App Communication between Android Apps Developed in App-Inventor and Android Studio - Allison, Lance; Fuad, Mohammad Muztaba (2016 IEEE/ACM International Conference on Mobile Software Engineering and Systems (MOBILESoft), 2016)
Communications between mobile apps are an important aspect of mobile platforms. Android is specifically designed with inter-app communication in mind and depends on this to provide different platform specific functionalities. Android Apps can either be designed with the help of Android SDK and using IDEs such as Android Studio or by using a browser based platform called App Inventor. These two development platforms provide their own technique for inter-app communication in the same platform, however lack an established method of inter-app communication when apps are developed using the two seperate development platforms. This paper provides the missing information required for the app communications and presents the method for sending and receiving arguments between apps developed in these two platforms. The paper also outlines the significance of the result, and examines their limitations.